HUBUNGAN PERILAKU PENCARIAN INFORMASI PEREMPUAN DENGAN KEBUTUHAN FASHION - Amanda, Cindy; Prijana, Prijana; Yanto, Andri (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2017)
This article analyzes about women’s information seeking behavior with fashion needs. The aim of the research is to recognize the information seeking behavior of woman for fashion needs, at the Faculty of Communication Sciences of Padjajaran University. The paradigm of this study is post-positivism with a quantitative approach. The method used is correlational with Pearson’s product-moment correlation statistic test. The population of this study are 92 people with accidental sampling technique. The result of this study concludes that the information seeking behavior of women is moderately related with fashion needs. The constantly developing fashion needs requires woman to search for information which will later form an information seeking behavior based on the intensity of media use.